(untitled) - World Bank (Washington, DC, 2022)
Chad faces enormous challenges: poverty, insecurity associated with fragility, conflict, and violence (FCV), and low access to basic services such as education, health, and drinking water. In addition, it is the world’s most vulnerable country to climate change, according to the Notre Dame Global Adaptation Initiative, 2021. In this challenging context, the COVID-19 crisis worsened economic difficulties, increased inequality, and plunged hundreds of thousands of Chadians in extreme poverty. Key environmental challenges include: (i) Land degradation; (ii) Waste management and (iii) Climate change.